Strategi Nafkah Petani Perkotaan Pulau Kecil (Studi Kasus Kecamatan Leitimur Selatan Kota Ambon) - August Ernst Pattiselanno; Edizon Jambormias; Junianita Fridianova Sopamena (Jurnal Sosial Humaniora, 2025)
Farmers who live along the coastal of a small island have various ways to fulfill their needs. The ways to fulfill their needs depend on various habits that have been carried out since a long time ago. The objective of this research is to analyze livelihood strategies designed by the societies in the small island. Research was located in South Leitumur District, Ambon City. The site of research was of two sub-districts, namely Hutumuri and Leahari. Sample of farmers were determined purposively from both sub-districts, resulting in 69 farmers, precisely 51 farmers in Hutumuri and 18 farmers in Leahari. Data were collected from depth interview and analyzed with simple tabulation accompanied with descriptive explanation. Result of the research indicated that there are three livelihood strategies designed by coastal communities in South Leitimur District, namely first, developing natural/farming resource potentials by increasing the quantity of commodities that have potential capability to satisfy daily necessities; second, developing natural/farming resource potentials in wider sense, which concerns with developing potentials of coastal area as fishing spot; and third developing human resource potentials by providing job opportunity out of farming and improving the existing skills owned by farmer household.